PENGARUH KADAR AIR SISI KERING DAN SISI BASAH TERHADAP PARAMETER KUAT GESER TANAH EKSPANSIF - Rina Yuliet (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2016)
Abstract : If the clay soil has been compacted on dry side of optimum moisture content, then the composition of the soil will not depend on the kind of compacting. Otherwise if the soil has been compacted on the wet side of optimum moisture content, it will affect the composition, shear strength and compressibility properties of soil. The aims of this study are to determine the effect of moisture content at dry side of optimum and wet side of optimum on the shear strength parameters for expansive soil. Expansive soil which is used as the sample is originally found in the area of Karangnunggal Tasikmalaya, West Java. The results of triaxial test conditions of unconsolidated - undrained without saturation and with saturation, shows that the clay soil compacted on the wet side of optimum will have a shear strength parameters lower than compacted soil on the dry side of optimum. It can be seen from the results of triaxial test conditions of unconsolidated - undrained without saturation on the dry side of optimum, the value of cohesion (c) is 1,2 kg / cm2 and the value of the friction angle (f) is 0.921o . Whereas on the wet side of optimum, shear strength parameters is 0.485 kg/cm2 and 0.348o for cohesion (c) and friction angle (f) respectively. Moreover, the results of triaxial test conditions of unconsolidated - undrained with saturation on the dry side of optimum yield the cohesion value ( c ) is 1,006 kg/cm2 and the value of the friction angle ( f ) 0.684o. While, on the wet side of optimum, the shear strength parameters is decreasing to 0148 kg/cm2 and 0.455o for cohesion (c) and friction angle (f) respectively.Keywords : dry side of optimum, wet side of optimum, shear strength, expansive soil.Abstrak : Jika tanah lempung dipadatkan pada kadar air sisi kering optimum, maka susunan tanah tidak akan bergantung pada macam pemadatannya, sedangkan bila tanah dipadatkan pada kadar air sisi basah optimum maka akan mempengaruhi susunan, kuat geser dan sifat kemampatan tanah. Penelitian ini bertujuan untuk mengetahui pengaruh kadar air sisi kering dan sisi basah optimum terhadap parameter kuat geser tanah lempung ekspansif. Tanah lempung ekspansif yang dijadikan sampel uji adalah tanah lempung di daerah Karangnunggal Tasikmalaya Jawa Barat. Hasil uji triaksial kondisi tak terkonsolidasi - tak teralirkan tanpa penjenuhan dan dengan penjenuhan, menunjukan bahwa tanah lempung yang dipadatkan pada sisi basah optimum akan memiliki parameter kuat geser yang lebih kecil dibandingkan tanah yang dipadatkan pada sisi kering optimum. Ini dapat dilihat dari hasil uji triaksial tak terkonsolidasi – tak teralirkan kondisi tanpa penjenuhan pada sisi kering optimum, nilai cohesi (c ) 1,2 kg/cm2 dan nilai sudut geser dalam (f) 0,921o. Sedangkan pada sisi basah optimum terjadi penurunan nilai parameter kuat geser tanah dimana nilai cohesi (c ) adalah 0,485 kg/cm2 dan nilai sudut geser dalam (f) adalah 0,348o. Hasil uji triaksial takterkonsolidasi – takteralirkan dengan penjenuhan pada sisi kering optimum nilai cohesi (c ) 1,006 kg/cm2 dan nilai sudut geser dalam (f) 0,684o. Sedangkan pada kondisi basah optimum terjadi penurunan nilai parameter kuat geser tanah dimana nilai cohesi (c ) 0,148 kg/cm2 dan nilai sudut geser dalam (f) 0,455o.Kata kunci : sisi kering optimum, sisi basah optimum, kuat geser, lempung ekspansif